Comparative Study of PAI in Schools in The 2013 and Independent Curriculum - Jias Mengki; Azhar Azhar (Innovative: Journal Of Social Science Research, 2023)
The 2013 curriculum aims to encourage students or students to be better at observing, asking questions, reasoning, and showing what they get or know after receiving learning material. The objects that become learning in structuring and perfecting the 2013 curriculum emphasize natural, social, artistic, and cultural phenomena. In contrast to the previous curriculum, the 2013 curriculum places more emphasis on the third aspect, namely producing students with high moral (affective), skilled (psychomotor), and knowledgeable (cognitive). Meanwhile, the independent curriculum is a curriculum that gives freedom to schools to explore their abilities according to the facilities, inputs, and resources they have and gives independence to teachers to convey essential and urgent material. The methodology used in this study is descriptive qualitative with language observations and actual information from various scientific journals that the implementation of the independent curriculum in PAI subjects is going well because the flow of the independent curriculum fits the character of PAI